2011
DOI: 10.1007/s11116-011-9322-4
|View full text |Cite
|
Sign up to set email alerts
|

Weekly activity-travel behaviour in rural Northern Ireland: differences by context and socio-demographic

Abstract: Travel behaviour, Transport disadvantage, Rural form, Social exclusion, Northern Ireland,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…A similar binary model has been used in other research contexts to identify the determinants of mode choice behaviour (Emond and Handy, 2012;Hine et al, 2012;Rose and Marfurt, 2007). Each outcome variable (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A similar binary model has been used in other research contexts to identify the determinants of mode choice behaviour (Emond and Handy, 2012;Hine et al, 2012;Rose and Marfurt, 2007). Each outcome variable (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown that the availability of different services and goods (e.g., diverse land uses) allows residents to participate in society (i.e., meets the residents' needs for recreation, jobs, health, social activities, etc. ), thus improving economic and social sustainability [7]. On the other hand, a lack of these opportunities encourages motorized travel, which affects environmental sustainability through, for example, noise and air pollution and climate change [8][9].…”
Section: Sustainable Neighborhoodsmentioning
confidence: 99%
“…Especially changes of weekdays and weekends are more different. The differences in rural areas were investigated by Hine et al (2012) concerning weekly activity behavior. Travel patterns were analyzed for different area accessibilities using questionnaires and travel diaries.…”
Section: Background Related Workmentioning
confidence: 99%